Tolerance and Intolerance of Muslims in Australia in Abdel-Fattah’s Does My Head Look Big in This? - Shofi Ayudiana; Muh. Arif Rokhman (Lexicon, 2019)
Australiais a multicultural country which claims themselves accept and respect the right of all people in Australia. However, its multiculturalism is questioned when the Australian people still treat Muslims with negative stereotypes and discrimination. This research examines the image of the Australian people towards Australian Muslims as represented in Randa Abdel-Fattah’s novel Does My Head Look Big in This? This study is a library research employing the theory of representation (Hall, 1997). The results show that the Australian people are both tolerant and intolerant to Muslims. People who are tolerant manifest their behaviors by having respectful attitudes, positive images of Muslims, and curiosity of Muslims and Islam. On the other hand, people who are intolerant express their behaviors in the forms of disrespectful attitudes, negative stereotypes, and discrimination towards Muslims.